Title: Recruitment is key to understanding amphibian's different population-level responses to chytrid fungus infection. (January 2020) - West, Matt; Todd, Charles R.; Gillespie, Graeme R.; McCarthy, Michael
Abstract: Understanding why related species have differing population-level responses to threats can be key to identifying conservation options for declining populations. However, this is difficult when multiple threats are implicated. Chytrid fungus ( Batrachochytrium dendrobatidis: Bd ) is implicated in at least 500 amphibian population declines globally, although few tangible options exist to mitigate pathogen impacts. Other threatening processes also invariably operate on most amphibians. Non-native fish, for example, can contribute to amphibian declines and may exacerbate Bd impacts. We disentangled the impacts of Bd and non-native fish upon two stream breeding frog species with differing conservation statuses to reveal vital rates that are crucial for species persistence. Litoria spenceri are threatened and historically occurred at elevations between 300–1100 m asl in southeastern Australia. Litoria lesueurii are non-threatened and sympatric with L. spenceri at some sites. Using mark-recapture derived demographic rates known to correlate with climate and elevation, discrete-time deterministic population models were constructed for each species at high, moderate and low elevation sites, and multiple management scenarios. Our study reveals that age to maturation, clutch size and egg-year 1 survival influenced interspecific and intraspecific population-level responses of the two frogs to Bd impacts. Importantly, our results highlight that an amphibian population's capacity to counteract Bd -mediated adult mortality is clearly constrained by other threats and environment interactions that moderate species recruitment. Furthermore, understanding limits to recruitment may help identify Bd mitigation strategies. In our study, disease mitigation may be best achieved at some sites by enhancing recruitment through non-native fish management.